Cisplatin treatment increases stemness through upregulation of hypoxia‐inducible factors by interleukin‐6 in non‐small cell lung cancer. Issue 6 (3rd May 2016) - Zhang, Fuquan; Duan, Shanzhou; Tsai, Ying; Keng, Peter C.; Chen, Yongbing; Lee, Soo Ok; Chen, Yuhchyau
Abstract : Cisplatin‐resistant A549 and H157 (A549CisR and H157CisR) non‐small cell lung cancer cells show increased stemness of cancer stem cells (CSCs) compared to their parental cells. We investigated whether interleukin‐6 (IL‐6) signaling contributes to this increased stemness in cisplatin‐resistant cells. When A549CisR and H157CisR cells were treated with neutralizing IL‐6 antibody, decreased cisplatin resistance was observed, whereas IL‐6 treatment of parental cells resulted in increased cisplatin resistance. Expression of the CSC markers was significantly upregulated in IL‐6‐expressing scramble cells ( in vitro ) and scramble cell‐derived tumor tissues ( in vivo ) after cisplatin treatment, but not in IL‐6 knocked down (IL‐6si) ( in vitro ) cells and in IL‐6si cell‐derived tumor tissues ( in vivo ), suggesting the importance of IL‐6 signaling in triggering increased stemness during cisplatin resistance development. Hypoxia inducible factors (HIFs) were upregulated by IL‐6 and responsible for the increased CSC stemness on cisplatin treatment. Mechanism dissection studies found that upregulation of HIFs by IL‐6 was through transcriptional control and inhibition of HIF degradation. Treatment of HIF inhibitor (FM19G11) abolished the upregulation of CSC markers and increased sphere formations in IL‐6 expressing cells on cisplatin treatment. In all, IL‐6‐mediated HIF upregulation is important in increasing stemness during cisplatin resistance development, and we suggest that the strategies of inhibiting IL‐6 signaling or its downstream HIF molecules can be used as future therapeutic approaches to target CSCs after cisplatin treatment for lung cancer. Abstract : IL‐6 mediated‐hypoxia inducible factor up‐regulation is important in increasing cancer stem cell numbers during cisplatin‐resistance development. We suggest that the strategies of inhibiting IL‐6 signaling or its downstream hypoxia inducible factor molecules can be used as future therapeutic approaches to block the cancer stem cell increase after cisplatin treatment in lung cancer.